BMPR2 mutation is a potential predisposing genetic risk factor for congenital heart disease associated pulmonary vascular disease. (15th May 2016) - Liu, Dong; Liu, Qian-Qian; Guan, Li-Hua; Jiang, Xin; Zhou, Da-xin; Beghetti, Maurice; Qu, Jie-Ming; Jing, Zhi-Cheng
Abstract: Background: Pulmonary arterial hypertension (PAH) frequently arises in patients with congenital heart disease (CHD) and can lead to pulmonary vascular disease (PVD). The present study was initiated to distinguish the predisposing effect of bone morphogenetic protein receptor 2 ( BMPR2 ) in CHD by comparing the different mutation features of BMPR2 between CHD patients with or without PVD. Methods and results: 294 CHD–PVD and 161 CHD without PVD patients were enrolled. PAH was diagnosed by heart catheterization at rest after CHD was first recognized by echocardiography. PVD was defined as a pulmonary vascular resistance (PVR) more than 3 Wood units. BMPR2 gene was screened by direct sequencing. A total of 24 mutations were identified, accounting for 22 of the 294 patients with CHD–PVD (7.5%) and 2 of the 161 CHD patients without PVD (1.2%, P  = 0.004). Female/male CHD–PVD patient ratio was 1.6:1, while in the BMPR2 mutation carriers female patients were more dominant (4.5:1, P  = 0.042). A significant higher BMPR2 mutation rate (12.6%) was found in repaired CHD–PVD ( P  = 0.010). BMPR2 mutations in CHD–PVD patients were identified in different clinical phenotypes. Missense mutation of BMPR2 is the dominant mutation type. Conclusion: Genetic predisposing factor may be an important component in the process of development of PVD in CHD patients. Female, repaired patients are more likely to be detected with genetic mutations.